2017
DOI: 10.15376/biores.12.1.1697-1705
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heat Treatment on the Water Uptake Behavior of Wood

Abstract: a Dimensional stability is an important property of wood that is strongly influenced by its water uptake behavior. Heat treatment is one method to improve wood dimensional stability. This study investigated the effects of heat treatment on the water uptake behavior of wood using a wicking test. The thickness of the tested wood sample was similar to that of the surface wood panel in a 3-layer composite floorboard. It was treated at different temperatures ranging from 200 °C to 400 °C under a nitrogen atmosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…The peak found at 1890 nm (in raw spectra) is most likely a combination of bound water and hemicelluloses; this peak was greatly reduced in EAPS and APS following drying. HWE results in decreased hygroscopicity, which explains the decreased absorption band intensity for EAPS [44]. This reduction in hygroscopicity is related to the removal of hemicellulose sugars, which represent the most hydrophilic constituent of lignocellulosics.…”
Section: Near Infrared Spectroscopy (Nirs) Of Aps and Eapsmentioning
confidence: 99%
“…The peak found at 1890 nm (in raw spectra) is most likely a combination of bound water and hemicelluloses; this peak was greatly reduced in EAPS and APS following drying. HWE results in decreased hygroscopicity, which explains the decreased absorption band intensity for EAPS [44]. This reduction in hygroscopicity is related to the removal of hemicellulose sugars, which represent the most hydrophilic constituent of lignocellulosics.…”
Section: Near Infrared Spectroscopy (Nirs) Of Aps and Eapsmentioning
confidence: 99%
“…High temperature reduces the EMC of wood [60], the veneer and, as a consequence, TS of plywood panels made from veneer [27]. Zhang et al [61] showed that changing the character of wood from hydrophilic to more hydrophobic by extracting hemicellulose can also potentially improve the dimensional stability of wood and wood composites. It is known that heat treatment causes a decrease in affinity of the treated material to water.…”
Section: Water Absorption and Thickness Swelling Of Plywood Samplesmentioning
confidence: 99%
“…e level of change depends on the wood species, type of heat treatment, treatment intensity, and process conditions, in which the temperature and the absence of oxygen play an important role [15]. As a result of these changes heat-treated wood has lower hygroscopicity [10,14,15], liquid water uptake [19][20][21][22][23], and consequently reduced dimensional changes. Besides, it was shown that the heat-treated wood has changed acidity, wettability, surface free energy, and anatomical structure.…”
Section: Heat-treated Wood As a Substrate For Coatingsmentioning
confidence: 99%